Plan de marketing para la empresa Guerrero y Asociados Jaga Comercio e Importaciones Cia. Ltda., para la ciudad de Loja, cantón Loja, provincia de Loja, para el año 2017. - Espejo Riofrío, Víctor Hugo (2018)
The research entitled Marketing plan for the company Guerrero y Asociados Jaga Comercio y Importaciones Cía. Ltda., For the city of Loja, canton Loja, province of Loja, for the year 2017 , was proposed with the aim of designing and proposing a marketing plan for this company in order to induce the efficiency of its activities for the increase of the utilities. Therefore, the methodology applied in the research work included the use of analytical, deductive, descriptive, synthetic, inductive and statistical methods, which were captured through the interview and survey techniques to obtain essential information that contributed to its development. This allowed us to detail the external diagnosis included in the PEST analysis and the quantitative examination of the five porter forces with an average sign that external factors have a great influence on the management of the company, which served as a basis to elaborate the matrix of evaluation of external factors - in reflection that the presented opportunities are not used correctly to counteract the threats. In a complementary manner, the matrix of evaluation of internal factors- EFI with a total of 2.31 was designed in an internal scope, which confirmed that there is a greater enhancement of weaknesses compared to the strengths and that they prevent the expansion of its market. Consequently, the SWOT analysis matrix was formulated from the matrix EFE and EFI previously exposed by mixing the strengths, opportunities, weaknesses and threats; that they based the elaboration of some strategies corresponding to: Elevation of the business image with the elaboration and implementation of the uniform of work for the personnel, Improvement of the quality of attention given to the clients with the elaboration and execution of a plan of training, Elevation of the recognition in the clients with the application of the promotion of delivery of a gift for each product purchased superior to $ 500.00, Increase of the positioning in the mind of the clients when doing publicity with the delivery of flyers and, Recruitment of a new niche market by expanding advertising with the creation and permanent updating of the website, and virtual networks of facebook, twitter and instagram. Therefore, these strategies were designed considering that they need to be implemented to improve the current positioning of the company and to be able to face the competition. Under this approach, the marketing plan was established, describing the strategic direction that included the main strategic objectives to meet a necessary investment value of $ 4910.00. As a result, it is concluded that the existing threats and weaknesses in the company that have a direct influence on its operation have prevented its income from being boosted, as a result of which it is recommended to execute the marketing plan prescribed in order to achieve its highest economic solvency.